Risk of chronic fatigue syndrome after COVID-19: A retrospective cohort study of 3227281 patients - Chen, Chih-Wei; Lee, Hsun-Hua; Chang, Shu-Hao; Chen, Yi-Ling; Wang, Yu-Hsun; Leong, Pui-Ying; Wei, James Cheng-Chung (Journal of infection and public health, 2024)
Many patients who recovered from COVID-19 still suffer from chronic fatigue syndrome (CFS). It was observed that patients with comorbidities were more prone to developing CFS. This research investigates the risk of post-COVID-19 CFS to assist healthcare professionals in reducing the risk of CFS. A retrospective cohort study is conducted to investigate the risk of post-COVID-19 CFS based on the TriNetX-sourced electronic health records. Factors including age, sex, race, vaccination, and severity of COVID-19 are analysed. Propensity score matching was applied to balance COVID-19 and non-COVID-19 cohorts. Kaplan-Meier analysis and Cox proportional hazard model were used to perform the relationship between COVID-19 and CFS risk. This research involved 3227281 patients with COVID-19 and 3227281 with non-COVID-19 between 1st January 2020 and 31st December 2023. The incidence of CFS was higher in the COVID-19 group compared to the non-COVID-19 group at 1 follow-up intervals (HR 1.59, 95 % CI = 1.54–1.63). Subgroup analysis revealed increased CFS risk across different age groups (>18), sexes, races, and comorbid conditions, with notable variations. COVID-19 patients have a higher risk of developing CFS compared to individuals without COVID-19. The increased risk is particularly significant in adults aged 18 years and older.